Physicochemical, Dough Volume and Microbial Growth during Leavening of Cassava-heat Composite Dough - Amapu, Tarfena; Dapiya, Hycinth; Onyimba, Isaac A.; Njoku, Andrew Ikechukwu; Gwanzhi, Danjuma; Mathew, Christiana Kataiko (Sahel Journal of Life Sciences FUDMA, 2024)
This study determined the impact of cassava inclusion on the physiochemical properties, dough volume, and microbial growth kinetics of cassava-wheat composite dough during leavening. A high-quality cassava flour (HQCF) proportions (10%, 20, 30%,40 and 50%) partially substituted the wheat flour for bread dough production were evaluated for pH, titratable acidity, dough volume, and microbial growth kinetics at 1-hour intervals. Overall, the dough volume progressively decreased with cassava inclusion which peaked at 84.00, 80.50, 74, 72.50, and 69.00 in 10%, 20%, 30%, 40%, and 50% cassava-wheat inclusion respectively during leavening. Cassava-wheat composite dough leavened with commercial yeast had the highest gas retention (85.50 cm3), followed by wheat dough co-fermented with amylolytic L. plantarum (AMz5), while cassava dough had the least (66.00 cm3). The 10% cassava-wheat composite dough had a dough volume comparable (p > 0.05) to the 100% wheat dough. The dynamics of dough-specific volume decreased with cassava inclusion in the order of 10% < 20% < 30% < 40% < 50%. The pH decreased from 4.75 to 3.60 in the wheat dough and from 5.30 to 4.50 in the composite dough during proofing. Moreover, the continuous growth of lactic acid bacteria decreased with cassava flour inclusion. Similarly, the baker’s yeast exhibited steady growth in the cassava-wheat composite dough with fermentation. This data indicates that using 10% or 20% cassava flour inclusion will provide dough with the leavening kinetics necessary for acceptable bread production.